Systematic literature reviews: Analisis angka buta huruf - Aprianti, Yusriah; Astuti, Alfira Mulya; Mulhamah, Mulhamah (Mathematic Education Departement, State Islamic University of Mataram, 2024)
Illiteracy is a big challenge in efforts to achieve the Sustainable Development Goals. This study aims to analyze the illiteracy rate in Indonesia from 2010 to 2024 using the Systematic Literature Review. The data in this study is in the form of articles sourced from Google Scholar and Dimensions AI. Articles were filtered with the Systematic Review Accelerator based on inclusion criteria. The data analysis technique uses VOSviewer and RStudio. The results of the study show that the trend of studying illiteracy in Indonesia fluctuates. Factors that affect the illiteracy rate, namely: pure elementary school participation rate, elementary school student-teacher ratio, open unemployment rate, percentage of poor population, percentage of malnourished toddlers, junior high school pure participation rate, percentage of junior high school educational facilities, percentage of junior high school educators, gross regional domestic product, percentage of households using computers/laptops, average length of schooling, number of educators, the percentage of residents have a mobile phone, and the percentage of areas with city status. Illiteracy figures are also affected by spatial effects. In addition, illiterate numbers have a simultaneous effect.